Spatio - temporal evolution trajectories and dynamic interactions of arable land multifunctionality in China’s major grain-producing regions - Xing, Xiaowei; Lu, Feng (Frontiers in Environmental Science, 2025)
Promoting the multifunctional utilization of arable land in major grain-producing regions has become a crucial measure for China to safeguard food production security. Systematically analyzing the developmental evolution characteristics and dynamic trade-off relationships of the various functions serves as the foundation for promoting arable land multifunctional utilization. Based on the constructed production-social-ecological multifunctional evaluation system, the entropy method, Kernel density estimation, Markov chain method and PVAR model are comprehensively employed to depict the empirical test. The results are as follows: (1) The production function, social function, and ecological function of arable land in the major grain-producing regions generally remain at relatively low levels overall, exhibiting distinct divergent evolutionary characteristics and heterogeneous spatial distribution patterns, with evident trade-offs among different functions across provinces. (2) While the overall disparities in all functions across the 13 grain-producing provinces have significantly narrowed, there exists a potential widening tendency in inter-provincial gaps for both production and social functions. (3) The inter-provincial differences in all three major functions demonstrate gradual, incremental dynamic evolution with strong state stability. (4) The dynamic utility pathways of the three functions of arable land are obviously different, and a mutually reinforcing interactive relationship exists between the production function and ecological function, whereas the both functions respectively exhibit inhibitory interactions with the social function. This paper effectively investigate the development levels, spatio - temporal evolution, and dynamic interactions among different arable land functions in major grain-producing regions, and provides empirical references for promoting interactive coordination among these functions.